PECULIARITIES OF PHYSICAL PROCESSES OF FORMATION OF SILICON SURFACE-BARRIER STRUCTURES - Gaidar, G.P.; Berdnichenko, S.V.; Vorobyov, V.G.; Kochkin, V.I.; Lastovetskiy, V.F.; Litovchenko, P.G. (Reports of the National Academy of Sciences of Ukraine, 2024)
Semiconductor detectors occupy a prominent place among nuclear spectrometry instruments and are used to study the spectral composition, intensity, spatial and angular distributions of ionizing particles. Silicon is the most attractive material for detector production due to the advanced silicon technology and the possibility of creating not only dosimetric and radiometric, but also spectrometric detectors. Silicon-based semiconductor detectors are used to detect charged particles, as well as gamma quanta, including those with an energy of less than 100 keV and X-ray radiation. The results of a comprehensive study of the properties of the initial high-resistive n-Si with the aim of improving the technology of manufacturing silicon spectrometric semiconductor detectors with predetermined parameters were generalized. For plane-parallel etching of silicon crystals, methods of chemical treatment of the Si surface have been developed by selecting the composition of etchants based on high-purity acids. A method of accelerated formation of surface-barrier structures by applying an external electric field at the stage of their formation was proposed. Conditions for holding the structures for optimal formation of high-quality and stable surface-barrier p—n junctions were determined. On the basis of an optimized surface-barrier technology using large-diameter high-resistance n-Si, dE/dx-detectors have been developed with a working area of 8 cm2 and a range of thicknesses of the sensitive area from tens of microns to a millimetre, with thin input and output “windows” and an energy resolution no worse than 100 keV. The obtained detectors can be used in consisting of telescopes in nuclear experiments involving heavy ions at low yields of reaction products.